Avaliação do sofrimento mental em acadêmicos do curso de graduação em Enfermagem - Sena, Fernanda Miranda de (2019)
University entrance represents a new moment in people's lives and can bring with them anguish, fears and insecurities, thus leading to the onset or worsening of symptoms of mental distress, which may lead to the onset of Common Mental Disorder. There are several instruments for identifying this mental suffering, including the Self-Reporting Questionnaire-20. The objective of this study was to characterize the socioeconomic profile of the students and to identify their mental suffering. The study uses data obtained through the application of a socioeconomic questionnaire and the Self-Reporting Questionnaire-20 instrument in 229 participants from June to July 2019. The data were tabulated in the Microsoft Excel® spreadsheet and analyzed through the Sigma Stat® 2.03 Statistical Program. Regarding the academic profile, it was observed that the majority (77,7%) are female, aged between 18 and 50 years old, have no partner (93,4%), and most of them (66, 8%) are practitioners of some religion. It was also found that 72,5% of the students are suffering from mental distress, with a predominance of positive responses to anxiety-depressive mood (62,8%) and decreased vital energy (61,5%). It was possible to conclude in the present study that there is a profile of young students, without partner and without children, predominantly female and through the application of the Self-Reporting Questionnaire-20 that most students have mental suffering.